Pengembangan Komoditas Unggulan Perkebunan Berbasis Modal Sosial dan Peluang Investasi di Aceh - Romano; Mujiburahmad; Ramayana; Ira Manyamsari (Program Studi Agribisnis Fakultas Pertanian Universitas Samudra, 2019)
Aceh development plantation focused in regional potential commodity development. The development to supported livelihood society dan agroindustry growth. This research did in Aceh with survey method and the analysis used hierarki model, LQ, investment criteria, specialization and diversification. Result showed that Aceh plantation development wasn’t suitable with potential production center in each district. The prime commodity in Aceh such as palm oil, coffee, cocoa, rubber, coconut and areca have been people mainstay as a source of livelihood in plantation sector. Main strategy from commodity development in Aceh wa a diversification strategy based on potential combination, commodity type and infrastructure to support agribusiness. Every district develop some commodity to anticipate price fluctuation.